Meteorological, hydrological and metabolism data measured in Laguna La Conceja (Ruidera, Spain) during 2009 - Salvador Sánchez-Carrillo (PANGAEA, 2018)
Meteorological, hydrological and metabolism data measured in Laguna La Conceja (Ruidera, Spain) during 2009. Data were used to study short-term biogenic carbon dynamics during mid stratification.